2011
DOI: 10.1002/ejoc.201001680
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Reactivity of Acyl Anion Equivalents: The Epoxide Ring Opening Case

Abstract: Acyl anion equivalents (umpolung) are the practitioner's first choice en route to 1,3‐hydroxy keto compounds from epoxides. Why? This investigation evaluates computationally and experimentally the reactivity of a near comprehensive range of acyl anion equivalents using epoxide ring opening as a test vehicle. Reactivity understanding, reactivity order, surprise failures in performance, along with unprecedented, but far from superior, reactivity of TosMIC is presented for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…[29] Silyl protection of the pendant hydroxyl group enabled enolate-mediated alkylation of ketone 28 with ethyl iodoacetate, which gave a mixture of diastereomers 29 and 30. The major diastereomer 30 was then reacted with the acyl anion equivalent, [30] lithium dithiazide (31) [31] to give lactone 32. Unmasking the aldehyde was performed using mercury acetate, and the final methyl enone was installed using ylid 33, to afford 34 (Scheme 4).…”
Section: Biomimetic Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…[29] Silyl protection of the pendant hydroxyl group enabled enolate-mediated alkylation of ketone 28 with ethyl iodoacetate, which gave a mixture of diastereomers 29 and 30. The major diastereomer 30 was then reacted with the acyl anion equivalent, [30] lithium dithiazide (31) [31] to give lactone 32. Unmasking the aldehyde was performed using mercury acetate, and the final methyl enone was installed using ylid 33, to afford 34 (Scheme 4).…”
Section: Biomimetic Synthesismentioning
confidence: 99%
“…[54] The corresponding ketone (72) initiated the first point of convergence, which was facilitated by considering acyl anion equivalent chemistry (i.e. 73), [30] which provided a left-(74) and right-(75) hand fragment. The left-hand fragment (74) could be further dissected using the same acyl anion approach to give epoxides 76 and 77, whereas the right-hand fragment (75) was perfectly poised for a ring-closing metathesis-styled disconnection leading to 78, which could be accessed from a functionalised syn-diol of the type seen in 79.…”
Section: Linear Synthesismentioning
confidence: 99%
“…Therefore, their investigation evaluated computationally and experimentally the reactivity of acyl anion equivalents in the epoxide ring opening. 81 Yadav and co-workers reported the stereoselective synthesis of the segment C 38 -C 54 of a marine metabolite halichondrin B.…”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…Furthermore, it was found that TosMIC (151) underwent reaction with only a select range of epoxides in moderate to good yields. 25 From these investigations, it became clear that sulfur functionality was very desirable in an AAE for epoxide ring-opening reactions. Furthermore, we found the oxida- tion state of sulfur to be of central importance, with reactivity and general performance decreasing as the oxidation state increased.…”
Section: Figure 5 Acyl Anion Equivalentsmentioning
confidence: 99%